2015
DOI: 10.1002/ana.24357
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian target of rapamycin pathway mutations cause hemimegalencephaly and focal cortical dysplasia

Abstract: Focal malformations of cortical development, including focal cortical dysplasia (FCD) and hemimegalencephaly (HME), are important causes of intractable childhood epilepsy. Using targeted and exome sequencing on DNA from resected brain samples and non-brain samples from 53 patients with FCD or HME, we identified pathogenic germline and mosaic mutations in multiple PI3K/AKT pathway genes in 9 patients, and a likely pathogenic variant in 1 additional patient. Our data confirm the association of DEPDC5 with sporad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
257
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 259 publications
(273 citation statements)
references
References 23 publications
12
257
1
3
Order By: Relevance
“…70 HME, which shares neuropathological features such as cytomegalic neurons and cortical dyslamination with FCDII, are also known to be associated with somatic mutations in PIK3CA, PIK3R2, AKT3, and MTOR, as well as germline mutations in PTEN and TSC2. 17,70 These genes encode wellknown regulators of the mTOR pathway, and their dysfunction can lead to aberrant activation of mTOR kinase. Together, these findings and the present results strongly suggest that hyperactivation of mTOR kinase by mutations in mTOR pathway genes underlies the molecular pathogenesis of FCD, which is the most common form of childhood intractable epilepsy and requires surgery as a treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…70 HME, which shares neuropathological features such as cytomegalic neurons and cortical dyslamination with FCDII, are also known to be associated with somatic mutations in PIK3CA, PIK3R2, AKT3, and MTOR, as well as germline mutations in PTEN and TSC2. 17,70 These genes encode wellknown regulators of the mTOR pathway, and their dysfunction can lead to aberrant activation of mTOR kinase. Together, these findings and the present results strongly suggest that hyperactivation of mTOR kinase by mutations in mTOR pathway genes underlies the molecular pathogenesis of FCD, which is the most common form of childhood intractable epilepsy and requires surgery as a treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Moreover, recent studies have reported that mosaic TSC1 or TSC2 mutations identified in blood and saliva can cause the milder clinical features of TSC. 20,21 Therefore, it is likely that somatic mutations in genes encoding these upstream regulators of mTOR kinase could be responsible for the development of FCDII in individuals who lack MTOR mutations.…”
Section: Introductionmentioning
confidence: 99%
“…TSC is naturally a mutation of either TSC1 or TSC2 in 85%, whereas more than half of those cases show also mosaicism 43. Recent studies found somatic (mosaic) mutations affecting the mTOR signaling also in focal lesions of FCD II patients 4, 8, 21, 25, 32, 36. This is a very important aspect since as far as we know, in FCD, the mutations are localized and show profound variability in cellular expression.…”
Section: Discussionmentioning
confidence: 99%
“…29 mTORC1 activation is not exclusive to epilepsy associated with TSC. Genes responsible for regulation of mTORC1 have been identified in epileptic patients with isolated focal cortical dysplasia IIb, 30,31 hemimegencephaly, 32 and syndromic epilepsies caused by DEPDEC5, 32,33 PTEN, 34 and STRADA. 35 Loss of mTORC1 regulation has been identified in animal models of acquired epilepsies, including temporal lobe epilepsy and posttraumatic epilepsy, which are responsive to sirolimus treatment.…”
Section: Classification Of Evidence This Interventional Study Providesmentioning
confidence: 99%